Benchmarking Financial Systems : Introducing the Financial Possibility Frontier - Beck, Thorsten; Feyen, Erik (World Bank, Washington, D.C., 2013)
Across the world, supply for financial services rarely matches the demand, given multiple market frictions. This paper discusses the concept of the financial possibilities frontier as a constrained optimum to categorize different problems of shallow financial markets or unsustainable expansion. The paper offers three examples of how to use different data sources to apply the frontier concept to assess the state of financial systems.